Foreign direct investment spillovers and productivity growth in Indonesian garment and electronics manufacturing - Suyanto; Bloch, Harry; Salim, Ruhul (Routledge, 2012)
Inflows of foreign direct investment generate externalities that spill over to domestic firms and raise their productivity. This article examines the extent of spillover effects of foreign direct investment for firms in the highly disaggregated garment (ISIC 3221) and electronics industries (ISIC 3832) in Indonesia. Both are export-intensive industries, but differ greatly in technological sophistication and labour intensity. Changes in both the productivity level and rate of growth in each industry are decomposed into the effects of technological change, technical efficiency change and scale efficiency change and then the impacts of spillovers on each component and on total productivity are estimated. The findings suggest that foreign direct investment generates a positive effect on total productivity change, technical efficiency change, technological change, and scale efficiency change in the garment industry. In contrast, foreign direct investment contributes significantly negatively to total productivity, technological change and scale efficiency change, but has no significant effect on technical efficiency change in the electronics industry.